A181 BODY MASS INDEX AND THE RISK OF ACUTE PANCREATITIS BY ETIOLOGY: A PROSPECTIVE COHORT STUDY IN KOREA. (15th March 2019) - Choi, J; Han, K; Yi, S; Lee, S
Abstract: Background: It is unclear whether obesity increases the incidence of acute pancreatitis (AP) in the general population. Further, no study has prospectively examined the associations of the risk of AP by etiology with measured body mass index (BMI) values. Aims: Through a large prospective cohort study that included 513 thousand participants in Korea, we set out to elucidate whether and to what extent the associations between measured BMI and AP exist and whether the associations differ by the etiology and the severity of AP. Methods: 512, 928 Korean participants in routine health examinations during 2002–2003 were followed up until 2013 via linkage to national hospital discharge records to assess AP incidence. Multivariable-adjusted hazard ratios (HRs) were calculated using BMI measurements. Results: During 10.5 mean years of follow-up, 1656 persons developed AP (337 gallstone-related and 1319 non-gallstone-related). Nonlinear associations were found: U-curves for total and non-gallstone-related AP, and a reverse L-curve for gallstone-related AP. Each 5 kg/m 2 increment in BMI increased gallstone-related AP by 123% (95% CI=48%-234%) and non-gallstone-related AP by 42% (9%-84%) in the range ≥25 kg/m 2 ( P heterogeneity =0.068). Obese persons had a doubled risk of gallstone-related AP compared to normal-weight persons. In the range <25 kg/m 2, BMI had an inverse association with non-gallstone-related AP, but no association with gallstone-related AP ( P heterogeneity <0.001). For non-gallstone-related AP, the HRs per each 5 kg/m 2 BMI increment were 0.50 (men), 0.73 (women), 0.46 (alcohol drinkers), 0.69 (alcohol non-drinkers), 0.43 (ever smokers), and 0.73 (never smokers). Conclusions: Gallstone-related and non-gallstone-related AP has different nonlinear associations with BMI. Higher BMI increases the risk of both gallstone-related and non-gallstone-related AP, but more strongly for gallstone-related AP. For non-gallstone-related AP, in the range <25 kg/m 2, BMI has inverse associations that were stronger in males, current alcohol drinkers, and ever smokers than in their counterparts. Funding Agencies: None